Integrating the Whoop It Up Strategy with the AIR (Auditory, Intellectually, Repetition) Learning Model in Arabic Language Learning - Taufik Taufik; Nailin Nabilah Febriani; Muhammad Afifudin Dimyathi; Rafidah Binti Hj Abdullah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
This research comprehensively describes implementing the